2021
DOI: 10.1029/2020ja028920
|View full text |Cite
|
Sign up to set email alerts
|

Bursty Ion Escape Fluxes at Mars

Abstract: Based on the Mars Atmosphere and Volatile EvolutioN (MAVEN) measurements we have observed cases when the fluxes of oxygen ions escaping the Martian ionosphere exceed their median values by more than a factor of 100. In the Martian tail very high fluxes of the more energetic (E > 30 eV) oxygen ions fill the plasma sheet which then becomes much broader than under conditions with median values of ion fluxes. We have analyzed the occurrence of such events in the upper ionosphere near the terminator plane, which is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
6
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 45 publications
2
6
0
1
Order By: Relevance
“…• Mars' magnetotail can be twisted up to 60 deg away from its expected location based on interplanetary magnetic field (IMF) draping, much greater than Earth's tail twist • MAVEN observations show that Mars' tail exhibits larger twisting for +B Y IMF orientation, compared to −B Y IMF • Mars crustal magnetic fields may play a significant role in shaping the twisted structure of the Martian magnetotail (Bowers et al, 2021;Hara et al, 2017). The Martian magnetotail also serves as a major pathway for atmospheric escape (e.g., Brain, Barabash, et al (2010); Dong et al (2017); Dubinin et al (2011Dubinin et al ( , 2021; Halekas et al (2016); Lundin (2011)).…”
mentioning
confidence: 99%
“…• Mars' magnetotail can be twisted up to 60 deg away from its expected location based on interplanetary magnetic field (IMF) draping, much greater than Earth's tail twist • MAVEN observations show that Mars' tail exhibits larger twisting for +B Y IMF orientation, compared to −B Y IMF • Mars crustal magnetic fields may play a significant role in shaping the twisted structure of the Martian magnetotail (Bowers et al, 2021;Hara et al, 2017). The Martian magnetotail also serves as a major pathway for atmospheric escape (e.g., Brain, Barabash, et al (2010); Dong et al (2017); Dubinin et al (2011Dubinin et al ( , 2021; Halekas et al (2016); Lundin (2011)).…”
mentioning
confidence: 99%
“…Thus, the ULF waves modulate the heavy ion plume and planetary ion acceleration very strongly locally. Strong local variations (more than two orders of magnitude with respect to the mean value) in the heavy ion escape have also been observed by MAVEN and occur often in the +E sw hemisphere (Dubinin et al, 2021). It was proposed that is related to waves and instabilities.…”
Section: Discussionmentioning
confidence: 87%
“…Several of the escape channels are associated with steady‐state acceleration mechanisms like the planetary ion pickup by the solar wind and the formation of the heavy ion plume (Dong et al., 2017; Futaana et al., 2017). In addition, also dynamical processes can affect planetary ion acceleration in induced magnetospheres (Dubinin et al., 2021; Jarvinen et al., 2020a; Luhmann et al., 1987; Lundin et al., 2011; Omidi et al., 2020). Especially, a foreshock is formed in the upstream region by backstreaming charged particle populations scattered near the bow shock (Brain et al., 2002; Eastwood et al., 2005; Mazelle et al., 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Ion escape through the tail or the wake region, however, should be inefficient because of Mars' obstruction. It has been reported that bursty and efficient ion escape processes exist in tail regions (Dubinin et al., 2012, 2021). A similar process occurs in the Venusian tail (Zhang et al., 2012), suggesting this process should be a common characteristic of unmagnetized planets.…”
Section: Introductionmentioning
confidence: 99%